HUBUNGAN PENDIDIKAN DAN PENGETAHUAN TENTANG GIZI PADA PASIEN GAGAL GINJAL KRONIK TERHADAP ASUPAN ENERGI DAN PROTEIN YANG MENJALANI HEMODIALISIS DI RS IMANUEL BANDAR LAMPUNG - Asep Jalaludin Saleh; Ajib Jayadi; Sukanti Handayani (Jurnal Ilmu Gizi Indonesia (JIGZI), 2023)
AbstractConstant Kidney Disappointment (CKD) is a condition that causes irreversible andirreversible decline in kidney function and the body ignores digestion and fluid andelectrolyte balance. The danger factor for persistent kidney failure is diabetes mellitus due toheredity and diet, while another dangerous factor that can cause it is hypertension. If itcontinues continuously, it can cause kidney work to be hampered. The purpose of this studywas to break the relationship between education and knowledge about nutrition of patientswith chronic kidney failure on energy and protein intake undergoing hemodialysis atIMANUEL Hospital Bandar Lampung in 2021. The research method used research analyticobservational approach with cross sectional study. The data was processed by Chi-squaretest and fishers exact test with a total of 60 samples. It shows that there is a relationshipbetween education, knowledge of nutrition and energy and protein intake with P value 0.05.Keywords: education, knowledge, energy_intake, protein_intake.